Keunggulan dan Fasilitas Pembelajaran di Yayasan Al-Ma’soem pada Masa Pandemi - Kinesti, Rakanita Dyah Ayu; Khasanah, Amliyah Maqshudatul; Makrufah, Lailatul; Rohayatun, Rohayatun; Nurfiani, Septiana; Aulia, Zakiyatul (Lembaga Yasin AlSys, 2021)
This study aims to analyze the advantages and learning facilities at the Al-Ma'soem foundation during the pandemic with industry-based education that started from high school and was developed through the principles of discipline and religion. Al-Ma'soem Foundation organizes educational programs at the level of TK, SD, SMP, SMA Full Day/Boarding School (Islamic boarding school for Al-Ma'soem-PSAM students) By looking at how to learn fun at the boarding school-based Al-Ma'soem foundation that can affect the learning intensity of a student with the following tips: 1). Create study groups with roommates, 2). Organize free time or independent study time to the maximum, 3). Organize student rooms to be more effective for the learning process,4). Study in an outdoor area that you think is conducive to learning with good dormitory facilities: 1 room occupied by 4-6 people and bathroom facilities in the room plus a mattress and wardrobe. Al-Ma;soem graduates can certainly memorize juz 30 and This is done so that students get excited again. This study aims to analyze the advantages and learning facilities at the Al-Ma'soem foundation during the pandemic with industry-based education that started from high school and was developed over time.